Metabolic Syndrome in Patients with Atherosclerotic Vascular Disease - Sadaf Zaman, Masood Ahmad, Mujeeb Khan , Lubna Meraj (Journal of Rawalpindi Medical College, 2016)
Background:To determine the frequency of metabolic syndrome (MetS) in patients having atherosclerotic vascular disease. Methods: In this cross sectional study 100 patients with atherosclerotic vascular disease were included. Patients were enquired about the presence of diabetes, hypertension, ischemic heart disease, symptoms of peripheral vascular disease and any history of ischemic stroke. Blood pressure and waist circumference were measured. Fasting blood sugar and lipid profile (triglyceride and HDL) were estimated. Results: The mean age of the patients was 53.97±9.95 years. Forty five percent were males. Seventy five percent presented with a history of ischemic heart disease, 19% presented with a history of ischemic stroke and 6% had peripheral vascular disease. Overall, 46% patients had metabolic syndrome. The mean age of the patients with MetS was significantly lower than the patients without MetS(p= 0.005). Among the 75 CAD patients 32 (42.7%) had MetS; among the 19 ischemic stroke patients 10 (52.6%) had MetS and among the 6 PVD patients 4 (66.7%) had MetS. This difference in the proportion of patients with MetS was not statistically significant(p=0.427). Conclusion: Nearly half of the patients with atherosclerotic vascular disease have metabolic syndrome.